Efek Nefroprotektor Ekstrak Daun Kemangi (Ocimum sanctum) Terhadap Kerusakan Sel Ginjal Mencit (Mus musculus) Yang Diinduksi Parasetamol - Basith, M Abdul; Listyaningsih, Endang; Handayani, Selfi (Nexus Biomedika, 2012)
Background: Today, consuming paracetamol as an analgesic antipyretic drugs hasÂ increased. Paracetamol which used in inappropriate dose has bad effect to our body, such as nefrotoxic. Basil leaf extract has antioxidant as a protection of free radicals and reducing NAPQI which produced by paracetamol. The objectives of this research are to know the nefroprotector effect and this research will shown the multilevel dose of basil leaf extract as a nefroprotector in the renal cell damage induced by parasetamol. Methods: This was experimental laboratory with the post test only controlled group design. Sample group consisted of male mice Swiss Webster, 2-3 month, + 20 g. Samples divided into 4 groups, each group has seven mice. Mice for control group (K) and the first treatment group (P1) were given aquades for 14 days. The second treatment group (P2) will be given basil leaf extract dose I for 14 days. The third treatment group (P3) will be given basil leaf extract dose II for 14 days. Paracetamol will be given to P1, P2, and P3, with dose 0,1 ml/20 gr weight of mice on the day 12, 13, and 14. Finally on day 15th, mice are sacrificed with neck dislocation then the renal of mice was made preparations with paraffin blocks methods and Hematoxillin Eosin staining. Renal cell damage observed and counted a mount of scored on renal histological karyopyknosis, karyorrhexis, and karyolysis. Data are analized by One-Way ANOVA test (Î±= 0,05) and continued by Post Hoc Multiple Comparisons test (LSD) (Î± = 0,05). Results: Result of One-Way ANOVA shown that there was a significant of degree between 4 groups. Result of LSD method there was a significant of degree between K-P1, K-P2, P1-P2, and P1-P3 groups; and also it wasnât a significant of degree between K-P3 and P2-P3. Conclusions: The basil leaf extracts was able to decrease the renal cell damaging of mice and the increase of basil leaf extracts dose followed by the increase of protection effect to the renal cell damaging of mice which is induced by paracetamol. Â Keywords: basil leaf extract, paracetamol, renal cell damage.Â